2018
DOI: 10.1183/16000617.0076-2017
|View full text |Cite
|
Sign up to set email alerts
|

Best supportive care for idiopathic pulmonary fibrosis: current gaps and future directions

Abstract: Best supportive care (BSC) is generally defined as all the interventions and the multiprofessional approach aimed to improve and optimise quality of life (QoL) in patients affected by progressive diseases. In this sense, it excludes and might be complementary to other interventions directly targeting the disease. BSC improves survival in patients with different types of cancer. Patients with idiopathic pulmonary fibrosis (IPF) experience a vast range of symptoms during the natural history of the disease and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 100 publications
0
45
0
2
Order By: Relevance
“…Previous studies using alternate patient reported outcomes to measure quality of life in IPF have similarly noted weak to moderate correlations with lung function measures, including the MRC dyspnoea scale, ATAQ-IPF and CAT [25-27]. Imperfect correlations indicate that lung function alone cannot account for all differences in patient reported outcomes, in combination they offer tremendous clinical value [28]. However, the MRC dyspnoea scale is one dimensional, ATAQ-IPF remains extensive at 75 items and CAT was developed for COPD, which at 8 items is convenient but may not have the sensitivity to capture IPF traits [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using alternate patient reported outcomes to measure quality of life in IPF have similarly noted weak to moderate correlations with lung function measures, including the MRC dyspnoea scale, ATAQ-IPF and CAT [25-27]. Imperfect correlations indicate that lung function alone cannot account for all differences in patient reported outcomes, in combination they offer tremendous clinical value [28]. However, the MRC dyspnoea scale is one dimensional, ATAQ-IPF remains extensive at 75 items and CAT was developed for COPD, which at 8 items is convenient but may not have the sensitivity to capture IPF traits [29].…”
Section: Discussionmentioning
confidence: 99%
“…The best supportive care would be the combination of interventions in a holistic multidisciplinary therapeutic approach that looks for improving wellbeing and QoL in patients suffering progressive and devastating illnesses, considering the different needs related to the disease, the personal or cultural believing and the physical and psychosocial state 31,65 . The best care in IPF and other pulmonary fibrotic diseases should be patient-centered and not only include an optimal anti-fibrotic approach but also any intervention that reduces the burden of the disease, helps to control drug-related adverse events, and enhances the physical and mental state of the patient, aimed at improving the QoL.…”
Section: Looking For the Best Supportive Carementioning
confidence: 99%
“…Talking about the end of life with the patient and caregivers remain a challenge in IPF and other lung fibrotic diseases; however it is useful to enable patients and families to make decisions in line with their values and preferences 16,65 . Although the integration of palliative care into non-malignant life-threatening disease is not routine, family members of patients that received care at home with hospice services were more likely to report a less harmful dying experience.…”
Section: Looking For the Best Supportive Carementioning
confidence: 99%
“…Once symptom burden is accurately assessed, there are a number of pharmacological and nonpharmacological therapies available to reduce symptom burden [6,10,11]. These include regular counselling, anxiolytic and anti-depressive medications, low-dose narcotics, pulmonary rehabilitation, supplemental oxygen therapy, and early referral to palliative care to alleviate symptom burden and address advance care planning, with the ultimate goal of improving quality of life [3,12,13].…”
Section: @Erspublicationsmentioning
confidence: 99%